Using intermediate energy knockout, pickup, and charge exchange reactions with invariant mass spectroscopy for investigating nuclear structure beyond the proton drip line - Sobotka, L. G.; Charity, R. J. (Frontiers in Physics, 2025)
The continuum structure of light p-rich elements has been extensively studied in recent years by invariant-mass spectroscopy. The feeble Coulomb barrier for light proton-rich nuclei makes proton decay an essential tool in this region not unlike alpha decay is in the trans-Pb region and neutron-deficient rare earths. Unlike binary alpha decay, the part of the Chart of the Nuclides this mini review will focus on can undergo decay into many-particle final states and invariant-mass spectroscopy is the frame-invariant and multi-particle replacement for simple binary alpha-particle spectroscopy. Here we highlight how pairing is reflected in the zig-zaggy pattern of the drip line, the decay of nuclides beyond the drip lines, and what the masses of nuclides exterior to the p-drip line have taught us about shell structure. In this context, the subtlety of removing the Wigner, or n-p congruence, energy when interpreting nucleon separation-energy systematics is discussed. We also present examples of where isospin symmetry is maintained in the continuum and where it is not.